ANÁLISE QUÍMICA DO LIXIVIADO DA ÁGUA DE XISTO EM UM LATOSSOLO VERMELHO ESCURO DISTRÓFICO - Stocco, Ana Paula (2009)
Industrial processes generate a series of products, often without applicability becomes waste that contribute to pollution of soil, air and water. Some products may be reused and / or processed into raw materials for other processes. In this context, analyzed the water of oil shale (a byproduct of the process of obtaining the oil shale) using an Instrumental techniques (UV / VIS; of Flame Photometry, Atomic Absorption, potentiometry) and Analytical (Permanganometria, complexometry with EDTA, Total Nitrogen by the Kjeldahl method). In water of shale it was found significant levels of some nutrients in the form elements available to the plant as the phosphate and sulfate, and total nitrogen content and high concentration of organic matter. The basic character of water in shale could assist in the correction of soil acidity. After testing of a column leaching in Oxisol in three different depths, the leachate was subjected to the same analysis for the water of oil shale. Data from atomic absorption spectroscopy revealed the shale of low water levels of calcium and magnesium, and concentrations of micronutrients such as zinc, manganese and iron, and low levels of lead, cadmium and chromium. Concentrations of calcium, magnesium and potassium in the form available to the plant were not detected. The analysis of the leachate showed that variation of pH was slightly acid, besides the reduction in the concentration of nitrogen, phosphate and sulfate and organic matter. Concentrations of calcium, magnesium and potassium in the form available to the plant that had not been detected before the percolation, the traditional methods of analysis, appear in the analysis of the leachate, indicating that the soil was removed during the process. Data of Atomic Absorption Spectroscopy indicate significant withdrawal of calcium, magnesium and potassium for the three soil depths, and the most superficial layer was the one with a greater quantity of calcium and magnesium. Another element that has undergone leaching and the iron concentration was high, with the layer deeper water by the leaching of shale occurred with greater intensity. The manganese was leached soil at all depths, and the deepest layer presented the highest content. The zinc was leached in greater proportion in the most superficial layer. Lead, cadmium and chromium in the leachate remained virtually the same concentrations in the water of oil shale, indicating that they were not incorporated into the soil. The copper remained constant in its concentration compared to leachate water from shale In general, all soil cations were leached by ground water from shale.